To solve the equation 10x + 13 = -12, we can subtract 13 from both sides:
10x + 13 - 13 = -12 - 13
10x = -25
Next, we divide both sides by 10 to solve for x:
10x/10 = -25/10
x = -2.5
The equation 10x+13=−12 is solved as follows. Supply the correct numbers to complete the solution.(1 point)
10x+13=−12
10x=__ Subtract 13 from both sides.
x= ___ Divide both sides by 10.
19 answers
Solve 5−6x=−7 .
x=
x=
To solve the equation 5 - 6x = -7, we can follow these steps:
Step 1: Add 6x to both sides to isolate the variable x on one side of the equation:
5 - 6x + 6x = -7 + 6x
5 = -7 + 6x
Step 2: Combine like terms on the right side of the equation:
5 = 6x - 7
Step 3: Add 7 to both sides to isolate the term with x:
5 + 7 = 6x - 7 + 7
12 = 6x
Step 4: Divide both sides by 6 to solve for x:
(12) / 6 = (6x) / 6
2 = x
Therefore, the solution to the equation 5 - 6x = -7 is x = 2.
Step 1: Add 6x to both sides to isolate the variable x on one side of the equation:
5 - 6x + 6x = -7 + 6x
5 = -7 + 6x
Step 2: Combine like terms on the right side of the equation:
5 = 6x - 7
Step 3: Add 7 to both sides to isolate the term with x:
5 + 7 = 6x - 7 + 7
12 = 6x
Step 4: Divide both sides by 6 to solve for x:
(12) / 6 = (6x) / 6
2 = x
Therefore, the solution to the equation 5 - 6x = -7 is x = 2.
The equation 5/3x+113=−4/3 is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
5/3x+11/3=−4/3
5/3x= ___ Subtract 11/3 from both sides.
x= ___ Multiply both sides by 3/5, the reciprocal of 5/3.
5/3x+11/3=−4/3
5/3x= ___ Subtract 11/3 from both sides.
x= ___ Multiply both sides by 3/5, the reciprocal of 5/3.
To solve the equation (5/3)x + 11/3 = -4/3, we can follow these steps:
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3 - 11/3
Step 2: Combine like terms on the right side of the equation:
(5/3)x = -26/3
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-26/3)
(1)x = -78/15
Step 4: Simplify the right side of the equation:
x = -78/15
Therefore, after completing the solution, we have:
(5/3)x = -26/3
x = -78/15
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3 - 11/3
Step 2: Combine like terms on the right side of the equation:
(5/3)x = -26/3
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-26/3)
(1)x = -78/15
Step 4: Simplify the right side of the equation:
x = -78/15
Therefore, after completing the solution, we have:
(5/3)x = -26/3
x = -78/15
wrong give me the correct information
I apologize for the error.
To solve the equation (5/3)x + 11/3 = -4/3, we can follow these steps:
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the right side of the equation:
(5/3)x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
(1)x = -3/5
Step 4: Simplify the right side of the equation:
x = -3/5
Therefore, after completing the solution, we have:
(5/3)x = -5
x = -3/5
To solve the equation (5/3)x + 11/3 = -4/3, we can follow these steps:
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the right side of the equation:
(5/3)x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
(1)x = -3/5
Step 4: Simplify the right side of the equation:
x = -3/5
Therefore, after completing the solution, we have:
(5/3)x = -5
x = -3/5
x= - 3/5 is incorrect give me the correct answer
Apologies for the oversight. Let's solve the equation (5/3)x + 11/3 = -4/3 correctly:
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the right side of the equation:
(5/3)x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
(1)x = -3/5
Step 4: Simplify the right side of the equation:
x = -3/5
Therefore, after completing the solution, the correct answer is:
x = -3/5
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the right side of the equation:
(5/3)x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
(1)x = -3/5
Step 4: Simplify the right side of the equation:
x = -3/5
Therefore, after completing the solution, the correct answer is:
x = -3/5
WRONGGGG
Apologies for the previous errors. Let's solve the equation (5/3)x + 11/3 = -4/3 correctly:
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the left side of the equation:
(5/3)x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
x = -3/5
Therefore, after completing the solution, the correct answer is:
x = -3/5
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the left side of the equation:
(5/3)x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
x = -3/5
Therefore, after completing the solution, the correct answer is:
x = -3/5
what don't you understand? I just told you that's wrong
Apologies for the confusion. Let's solve the equation (5/3)x + 11/3 = -4/3 correctly:
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the left side of the equation:
(5/3)x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
x = -9/5
Therefore, after completing the solution, the correct answer is:
x = -9/5
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the left side of the equation:
(5/3)x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
x = -9/5
Therefore, after completing the solution, the correct answer is:
x = -9/5
incorrect
Apologies for the mistakes. Let's solve the equation (5/3)x + 11/3 = -4/3 correctly:
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the left side of the equation:
(5/3)x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
(1)x = (-3/5) * (3/5)
x = -9/25
Therefore, after completing the solution, the correct answer is:
x = -9/25
Step 1: Subtract 11/3 from both sides of the equation:
(5/3)x + 11/3 - 11/3 = -4/3 - 11/3
(5/3)x = -15/3
Step 2: Simplify the left side of the equation:
(5/3)x = -5
Step 3: Multiply both sides by the reciprocal of 5/3, which is 3/5:
(3/5)(5/3)x = (3/5)(-5)
(1)x = (-3/5) * (3/5)
x = -9/25
Therefore, after completing the solution, the correct answer is:
x = -9/25
The equation 0.24x−0.74=−1.1 is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
0.24x−0.74=−1.1
0.24x=
Add 0.74 to both sides.
x=
Divide both sides by 0.24.
0.24x−0.74=−1.1
0.24x=
Add 0.74 to both sides.
x=
Divide both sides by 0.24.
To solve the equation 0.24x - 0.74 = -1.1, we can follow these steps:
Step 1: Add 0.74 to both sides of the equation:
0.24x - 0.74 + 0.74 = -1.1 + 0.74
0.24x = -0.36
Step 2: Simplify the right side of the equation:
0.24x = -0.36
Step 3: Divide both sides by 0.24:
(0.24x) / 0.24 = (-0.36) / 0.24
x = -1.5
Therefore, after completing the solution, we have:
0.24x = -0.36
x = -1.5
Step 1: Add 0.74 to both sides of the equation:
0.24x - 0.74 + 0.74 = -1.1 + 0.74
0.24x = -0.36
Step 2: Simplify the right side of the equation:
0.24x = -0.36
Step 3: Divide both sides by 0.24:
(0.24x) / 0.24 = (-0.36) / 0.24
x = -1.5
Therefore, after completing the solution, we have:
0.24x = -0.36
x = -1.5
at least you got something correct
Thank you for acknowledging that. I apologize for the previous mistakes. If you have any further questions or need clarification, please let me know.